Effects of mild gestational diabetes mellitus on quality of umbilical cord blood hematopoietic stem cells procured at delivery - Ahmed, Sara. M.El. (2018)
Hematopoietic stem cell (HSC) transplantation persists as the most successful and effective curative therapy for many haematological and non-haematological diseases, and cord blood HSCs have considerable advantages compared to other sources. The low number of cells harvested restricts their use and hence successful engraftment is highly dependent on the quality and quantity of stem cells and nucleated cells in cord blood. Forasmuch, the higher costs of cryopreservation that is needed to store the blood units, it is important to determine the maternal and neonatal factors, which include maternal illnesses that influence the higher yield of hematopoietic stem cells obtained from umbilical cord blood. Hence, a wise decision of storing UCB for the definitive aim of successful cells engraftment can be made. This study evaluated the effect of mild Gestational Diabetes Mellitus (mGDM) on the quality and quantity of UCB parameters in terms of CD34+ cell count and viability, a total number of nucleated cells and cord blood volume. 130 samples of umbilical cord blood collected from Malaysian women who delivered their babies at Hospital Serdang between May 2016 and April 2017 were collected; 63 were mGDM and 67 were from healthy women. The harvesting of the umbilical cord blood was performed via the in utero method. The UCB samples analysis include the total UCB collected volume, total nucleated cell (TNC) count, and CD34+ cell count by flow cytometry following the ISHAGE protocol and the measurement of the viability resorting to the nucleic acid marker 7-amino actinomycin D. There was a significant statistical association between the healthy group and mGDM women group in terms of UCB unit volume and TNC number and viability. The mean UCB volume for healthy women was 60.88 ± 18.16, while it was 54.06 ± 19.40 in mGDM women (p = 0.041). The mean of TNCs was 54.84 ± 26.79, 44.42 ± 24.13 and viability of TNCs was 53.71 ± 25.52, 42.88 ± 24.12 (p = 0.022 and 0.014) for healthy women and mGDM women respectively. Nevertheless, the analysis of CD34+ count and its viability between the two groups yielded no significant statistical difference. On the other hand, the means of CD34+ percentage in mGDM (0.16 ± 0.19) was statistically significant when compared to healthy group (0.11 ± 0.10) with p = 0.027, which reflect that mGDM, yielded a higher % of CD34+. The correlation coefficients for CD34+ indicated a significant and positive relationship between placental weight and CD34+ cells counts (r = 0.572, p < 0.001), CD34+ viability (r = 0.279, p = 0.027), and CD34+ percent (r = 0.422, p = 0.001). UCB volume and TNCs count and viability are highly significantly related to the placental weight when r correlation coefficient values were 0.438 (p < 0.0010), 0.3810 (p = 0.002), and 0.382 (p = 0.002) respectively. On contrary, in the healthy group, placental weight only correlates to CB volume and TNC number with r = 0.288 (p = 0.019) and 0.246 (p = 0.047) respectively. The study revealed that gender has no significant impact on all UCB parameters regardless mothers of mGDM group or healthy group as (p > 0.05). Infant’s birth weight in the mGDM group has a positive correlation with UCB volume, TNC count and viability, but not CD34+ parameters (count, viability and percentage) (p > 0.05). As compared to neonates with normal birth weight (NBW) have higher blood volume, TNC count and viability, than low birth weight (LBW) neonates (p = 0.007, 0.010, 0.013). In the healthy group, all UCB parameters are not affected whether neonates are NBW or LBW (p > 0.05). In conclusion, mGDM has a negative impact on the UCB volume and TNC count and viability obtained from cord blood at delivery, but not on the yield of HSC. Placental weight and neonatal birth weight are the most important factors influencing the numbers of cord blood HSC. These findings would provide guidance to mothers who are GDM on diet control and to their health care providers in making the right decision regarding UCB stem cell collection and banking.